Spissiomyces endophytica (Dothideomycetes, Ascomycota), a new endophytic fungus from Thailand - Nakarin Suwannarach (2018)
© 2018 Magnolia Press. A new species of endophytic fungi, described herein as Spissiomyces endophytica, was isolated from tubers of Balanophora fungosa in Lampang Province, Thailand. A morphological investigation revealed that this species was distinguished from the previously described Spissiomyces species by its lager conidial size. Phylogenetic analysis was performed using combined sequence datasets of the small subunit (SSU), large subunit (LSU) and internal transcribed spacers (ITS) of the nuclear ribosomal DNA (rDNA), a part of the RNA polymerase (RPB2) and β-tubulin (TUB) genes, in order to support the morphological results. A full description, illustrations, phylogenetic tree and key to the species are provided.